Influence Interpersonal Communication and Discipline Work Against Employee Performance with Satisfaction Work As Intervening Variables at Pt. Permodalan Nasional Madani Sukabumi Branch - M Resya Apriansyah; Agus Salim (Greenation International Journal of Economics and Accounting, 2023)
This research was conducted to analyze the effect of interpersonal communication and work discipline on employee performance with job satisfaction as an intervening variable at PT. Permodalan Nasional Madani Sukabumi Branch. The sampling technique used non-probability sampling with saturated sampling technique (census) with a sample of 92 people. Data were obtained using questionnaires, interviews and literature studies to obtain complete and valid data. The data analysis technique used the Smart Partial Least Square (Smart-PLS) Structural Equation Modeling (SEM) condition model. The results showed that both interpersonal communication and work discipline simultaneously had a significant impact, in part, on PT. Permodalan Nasional Madani Sukabumi Branch. Researchers suggest that interpersonal communication and employee work discipline are two key factors in her that business leaders need to look out for.